Energy-dependent, high-affinity transport of nickel by the acetogen Clostridium thermoaceticum. - Lundie, L L (1988)
The nickel transport system of Clostridium thermoaceticum was investigated with 63NiCl2 and an anaerobic microfiltration transport assay. Transport was optimal at pH 7 to pH 7.5 and 65 degrees C and decreased in the presence of metabolic uncouplers and inhibitors. Exogenous nickel was concentrated 3,000-fold over the apparent nickel concentration gradient during typical transport assays. Stored cellular energy appeared to provide a short-term energy source to power nickel transport, and starvation experiments demonstrated external energy source stimulation of nickel translocation. The apparent Km and Vmax for nickel transport by carbon monoxide-dependent chemolithotrophic cells approximated 3.2 microM Ni and 400 pmol of Ni transported per min per mg of cells (dry weight), respectively. Magnesium, calcium, cobalt, iron, manganese, and zinc did not inhibit the transport of nickel.